Untested and undiagnosed: barriers to HIV testing among men who have sex with men, Beijing, China. Issue 3 (8th December 2011) - Li, Xuefeng; Lu, Hongyan; Raymond, H F; Sun, Yanming; Jia, Yujiang; He, Xiong; Fan, Song; Shao, Yiming; McFarland, Willi; Xiao, Yan; Ruan, Yuhua
Abstract : Objectives: Undiagnosed HIV presents great potential for the spread of infection. The authors identify the prevalence and correlates of never testing and being unaware of HIV infection in Beijing men who have sex with men (MSM). Methods: Cross-sectional biological and behavioural survey using respondent-driven sampling; 500 MSM were included. Results: HIV prevalence was 7.2% with 86.1% unaware of their infection; 33.2% had never tested. Never testing was associated with lower educational (adjusted odds ratio (AOR) 1.6, 95% CI (CI) 1.1 to 2.5), living in Beijing for ≤3 years (AOR 1.5, 95% CI 1.0 to 2.3), unprotected anal intercourse with most recent male partner (AOR 1.6, 95% CI 1.0 to 2.4), being unaware of the most recent male partner's HIV status (AOR 3.6, 95% CI 2.1 to 6.1) and holding stigmatised attitudes towards persons with HIV (AOR 1.1 per scale point, 95% CI 1.0 to 1.1). Predictors of having undiagnosed HIV infection were being married (AOR 2.4, 95% CI 1.0 to 5.4), living in Beijing for ≤3 years (AOR 3.6, 95% CI 1.5 to 8.4), being unaware of the most recent male partner's HIV status (AOR 6.8, 95% CI 0.9 to 51.6) and holding negative attitudes towards safe sex (AOR 1.1 per scale point, 95% CI 1.0 to 1.1). Conclusions: Recent attention has focused on HIV prevention interventions that depend upon knowing one's serostatus, including viral load suppression, prevention with positives, pre-exposure prophylaxis and seroadaptation. Until the low level of testing and resulting high level of undiagnosed HIV infection are addressed, these tools are not likely to be effective for MSM in China.